Mortality in Africa: An Introductory Overview - Carvalho, Ana Pires de (Africana Studia, 2020)
The knowledge of mortality levels, causes and differentials contributes to the understanding of population dynamics, its fragilities and development trends. It is also important to know their evolution over time. An elementary characteristic of a developed society is that people live long and healthy lives. This is not, however, the situation in Africa, where deep political, economic and social changes have been taken place for the last decades and there is a great variation of mortality levels over time and between regions. Even the mortality causes and differentials vary over time and from region to region. The paper intents to make an introduction to the mortality situation in Africa and presents its evolution and tendencies. It also points out to the overarching need for its more and better study. Key-words: Mortality; Mortality causes; Mortality differentials; Mortality rates; Africa